A rare cause of syndromic short stature: 3M syndrome in three families. Issue 2 (30th November 2020) - Isik, Esra; Arican, Duygu; Atik, Tahir; Ooi, Joo Enn; Darcan, Sukran; Ozen, Samim; Simsek Kiper, Pelin Ozlem; Utine, Eda; Cogulu, Ozgur; Ozkinay, Ferda
Abstract: 3M syndrome is a rare autosomal recessive genetic disorder characterized by severe growth retardation, dysmorphic facial features, skeletal dysplasia, and normal intelligence. Variants in CUL7, OBSL1, and CCDC8 genes have been reported to be responsible for this syndrome. In this study, the clinical and molecular findings of four 3M syndrome cases from three families are presented. All cases had growth retardation, relative macrocephaly, and typical dysmorphic facial features. Their neurological developments were normal. Sequencing of CUL7, OBSL1, and CCDC8 genes revealed two different novel homozygous variants in CUL7 in Families 1 and 3 and a previously reported homozygous pathogenic variant in OBSL1 in Family 2. In conclusion, a comprehensive dysmorphological evaluation should be obtained in individuals presenting with short stature and in such individuals with typical facial and skeletal findings, 3M syndrome should be considered. Our report expands the genotype of 3M syndrome and emphasizes the importance of thorough physical and dysmorphological examination.